Near Net Shape Manufacturing Processes - Gupta, Kapil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers the mechanism, salient features, and important aspects of various subtractive, additive, forming and hybrid techniques to manufacture near net-shaped products. The latest research in this area as well as possible future research are also highlighted. .
Towards the manufacturing of near net shape medical prostheses in polymeric sheet by incremental sheet forming -- Developments in Friction Stir Processing - A near net shape forming technique -- Evolution in Additive Manufacturing Techniques for Net-Shaped Metal Products -- Near Net Shape Manufacturing of Dental Implants using Additive Processes -- Laser additive manufacturing processes for near-net shape components -- Near Net Shape Manufacturing of Miniature Spur Brass Gears by Abrasive Water Jet Machining -- Fracture Forming Limits for Near Net Shape Forming of Sheet Metals -- Advances in Near-Net Shape Polymer Manufacturing through Microcellular Injection Moulding.
Keywords: Manufactures; Metals; Materials; Machines, Tools, Processes; Metals and Alloys; Materials Engineering